2014
DOI: 10.1039/c4ay01151a
|View full text |Cite
|
Sign up to set email alerts
|

Classification and differentiation of agarwoods by using non-targeted HS-SPME-GC/MS and multivariate analysis

Abstract: Agarwood and its related products are important, useful and valuable for many applications, such as medicine, incense, and perfume. In general, the grading method of agarwood is based on its physical properties, which is inefficient, time consuming and lacks repeatability. In this study, non-targeted headspace solid-phase microextraction (HS-SPME) combined with gas chromatography/mass spectrometry (GC/MS) and multivariate analysis was developed to classify and differentiate agarwoods based on their aromatic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…However, analysis of chemical constituents in agarwood solvent extracts is not suitable for differentiation of agarwood because agarwood is usually used to produce incense smoke. A few research studies analyzed chemical ingredients in the incense smoke produced by heated agarwood [ 11 , 18 , 19 ]. For example, Ishihara et al [ 11 ] analyzed chemical constituents in the incense smoke that was trapped in the Tenax TA adsorbent resin, and extracted in diethyl ether for GC and GC-mass spectrometry (MS) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of chemical constituents in agarwood solvent extracts is not suitable for differentiation of agarwood because agarwood is usually used to produce incense smoke. A few research studies analyzed chemical ingredients in the incense smoke produced by heated agarwood [ 11 , 18 , 19 ]. For example, Ishihara et al [ 11 ] analyzed chemical constituents in the incense smoke that was trapped in the Tenax TA adsorbent resin, and extracted in diethyl ether for GC and GC-mass spectrometry (MS) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also showed that high grade gaharu contained high levels of 10-epi-γ-eudesmol, aromadendrane, β-agarofuran, α-agarofuran, γ-eudesmol, epoxybulnesene and α-guaiene [ 24 , 25 , 26 , 27 ]. Meanwhile, Hung et al [ 28 ] found that α-copaene, trans -caryophyllene, and δ-guaiene were present in the most expensive agarwood powders/extracts. Although these studies have provided useful insights into the chemical profile of gaharu, more information is needed in order to make meaningful correlations between chemical constituents and the quality of gaharu.…”
Section: Introductionmentioning
confidence: 99%
“…It combines the use of analytical measurements (e.g., FTIR, 1 H-NMR, GC-MS, LC-MS) and multivariate data analysis to classify and identify metabolites in biological samples [ 29 , 30 , 31 , 32 ]. Previously, metabolomics has been successfully used to classify different grades of agarwood powder [ 28 , 33 , 34 ] and oils [ 34 , 35 , 36 ]. The analytical tools used in these studies were mainly GC-MS [ 33 , 34 , 35 ], GC-MS coupled with solid-phase microextraction (SPME) [ 22 , 24 , 25 , 27 , 28 ] and two-dimensional GC coupled to accurate mass time-of-flight mass spectrometry (TOFMS) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach helps highlight certain regions of the chromatogram which is important when interpreted simultaneously with the entire peak profile. TIC has been applied successfully for predicting the composition of biodiesel blends (Pierce et al, 2011), classifying edible oil type (Bagur-González et al, 2015), discriminating counterfeit medicines (Custers et al, 2014) or classifying and differentiating agarwoods (Hung et al, 2014). These studies confirmed this method as a high-throughput fingerprint analysis technique (Pierce et al, 2011), as valuable tools to discriminate between genuine and counterfeit medicines (Bagur-González et al, 2015) or as a simple, convenient and robust method to extract volatile compounds successfully for evaluating agarwoods and sandalwoods (Hung et al, 2014).…”
Section: Volatiles Analysismentioning
confidence: 51%